Cloacal exstrophy with vesicoureteric junction obstruction: Rare association - Amit Singh; Minu Bajpai; Abid Ali (Wolters Kluwer Medknow Publications, 2013)
Cloacal exstrophy is an extremely rare congenital abnormality resulting in an exstrophy of the urinary, intestinal and genital organs and associated with anomalies of other organ systems. We report a complicated case of cloacal exstrophy associated with right vesicoureteric junction obstruction.